METODE PEMBELAJARAN DISCOVERY TERBIMBING UNTUK MENINGKATKAN HASIL BELAJAR IPA PADA SISWA KELAS VII.1 SMP NEGERI 01 MUARA BUNGO TAHUN PELAJARAN 2018/2019 - FIVE YANTI (Jurnal Tunas Pendidikan, 2020)
Abstract This study aims to improve the science learning outcomes of class VIII students of SMP Negeri 01 Muara Bungo using guided discovery learning methods. This type of research is classroom action research. The subjects of this study were students of class VII.1 State Junior High School 01 Muara Bungo, totaling 28 students, consisting of 13 male students and 15 female students. Researchers used an action research model from Kemmis and Taggart. This research was conducted in two cycles of action. In the first cycle, it was conducted in one meeting, while in the second cycle there were two meetings. In each cycle there are planning, implementation, observation and reflection activities. The instruments used were observation sheets and tests. Before being used in the study, the test was empirically validated and with expert judgment. The reliability of the test was calculated using Alpha Cronbach. Observation data were analyzed descriptively qualitatively while test results were analyzed descriptively quantitative percentage. The results of the first cycle research showed that the percentage of students whose grades were above the KKM had only reached 71.43%, so they still could not reach the criteria for research success. In the second cycle, the steps for applying discovery learning methods to increase student success were carried out by providing motivation, dividing the number of smaller group members and heterogeneous members of the group, and giving the opportunity to make group presentations on the results of their practicum in front of the class. The percentage of student scores above the KKM in cycle II increased to 89.29%. Based on the research results, it can be seen that the guided survey method can improve science learning outcomes. Keywords: methods, learning, guided discovery, science